A 65 Year Retrospective on Social Sciences Research in Sri Lanka: An Analysis of Scopus Indexed Publications - Chandani, J.G.; Nishanthi, H.D.M (Lattice Science Publication (LSP), 2025)
This article analyzes 65 years (1952-2024) of research conducted by Sri Lankan scholars in the field of Social Sciences. The study's objective was to assess the research contributions of authors in Social Sciences (SS) affiliated with the 17 public universities overseen by the University Grants Commission (UGC) of Sri Lanka. The bibliometric method was employed to evaluate the research performance of authors linked to Sri Lankan universities. The Elsevier Scopus database was chosen for extracting data, using "Sri Lanka" as the search term for affiliations. Data was gathered from 17 universities categorized under "Social Sciences." A total of 3,953 research articles (6.1%) were retrieved from the database pertaining to SS. Each entry was verified twice, leading to the removal of 29 duplicate records. This study offers a thorough bibliometric examination of 65 years of social science research in Sri Lanka, concentrating on scholarly publications from 17 public universities. Utilizing the Elsevier Scopus database provides insights into the research output, development trends, and growth patterns among Sri Lankan scholars in the Social Sciences. The results indicate a rising trajectory, with a significant increase in publications following the Covid-19 pandemic. This research will aid future scholars in pinpointing less-explored areas and support policymakers in determining research funding priorities. It represents the first comprehensive analysis of the social science research landscape in Sri Lanka.
Keywords: Social Sciences Research, Trends and Development, Universities, Bibliometrics, Sri Lanka